Tropical Fruit Growers' Water Use and Conservation Practices in Miami-Dade County - Rafael Muñoz-Carpena; Jonathan H. Crane; Glenn D. Israel; Carlos F. Balerdi (EDIS)
This fact sheet reports water conservation trends for tropical fruit producers based on an extensive survey carried out in Miami-Dade County. This document is Fact Sheet ABE345, one of a series of the Agricultural and Biological Engineering Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published December 2003.